1990
DOI: 10.1111/j.1744-6570.1990.tb02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of Two Categories of Assessment Center Dimension Ratings

Abstract: The construct validity of assessment center final dimension ratings was examined within a nomological network of cognitive and personality measures. Four hundred forty-one employees of a large mid-western petroleum company were assessed on 11 dimensions in two broad categories and completed four tests. Results showed that several cognitive ability measures related more strongly to performance-style dimension ratings than to interpersonal-style dimension ratings, providing evidence for convergent and discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
2
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 31 publications
3
96
2
4
Order By: Relevance
“…Past research that studied the nomological network of AC ratings involved the overall assessment rating (e.g., Collins et al, 2003), final dimension ratings (Dilchert & Ones, 2009;Meriac, Hoffman, & Woehr, 2014;Shore, Thornton, & Shore, 1990), overall exercise ratings (Hoffman, Kennedy, LoPilato, Monahan & Lance, 2015), or latent exercise factors together with the latent general performance factor (Lance et al, 2007) and their relationships with the Big Five and general mental ability (GMA). However, this research allows only limited inferences with regard to the constructrelated validity of the different latent components that constitute AC performance, namely, dimensions, exercises, and general performance (Hoffman et al, 2011) relative to each other.…”
Section: Nomological Network Of Ac Factorsmentioning
confidence: 99%
“…Past research that studied the nomological network of AC ratings involved the overall assessment rating (e.g., Collins et al, 2003), final dimension ratings (Dilchert & Ones, 2009;Meriac, Hoffman, & Woehr, 2014;Shore, Thornton, & Shore, 1990), overall exercise ratings (Hoffman, Kennedy, LoPilato, Monahan & Lance, 2015), or latent exercise factors together with the latent general performance factor (Lance et al, 2007) and their relationships with the Big Five and general mental ability (GMA). However, this research allows only limited inferences with regard to the constructrelated validity of the different latent components that constitute AC performance, namely, dimensions, exercises, and general performance (Hoffman et al, 2011) relative to each other.…”
Section: Nomological Network Of Ac Factorsmentioning
confidence: 99%
“…But, in addition, they agree wel1 with fïndings from research (as discussed above) into determinants of career advancement in management. And moreover, they correspond closely with results from research into the basic dimensions that, generally, underlie assessment center ratings (Sagie & Magnezy, 1997;Scholz & Schuier, 1993;Shore, Thomton & McFarlane Shore, 1990). In every step of the selection procedure, these rather broad dimensional categories are elucidated by corresponding behavioral samples or 'anchors' of the dimensions.…”
Section: Selection Dimensionsmentioning
confidence: 99%
“…One study that found evidence of construct validity for AC dimension ratings is Shore, Thornton and Shore (1990). They investigated the validity of these ratings using measures of personality and cognitive ability within a nomological network.…”
Section: Introductionmentioning
confidence: 98%
“…Using this unified model of validity, the present study investigated the construct validity of ratings from a developmental AC. The nomological network approach used by Shore et al (1990) appears to be a suitable method for studying construct validity. By enlarging this network to include measures of job performance in addition to personality, the present study attempts to provide stronger evidence of construct validity for assessment centers.…”
Section: Introductionmentioning
confidence: 99%